ANALISIS KELAYAKAN DAN STRATEGI PENGEMBANGAN USAHA BUDIDAYA IKAN AIR TAWAR DI KABUPATEN SLEMAN - Siti Hariati Yuwani; Irham Irham; Jamhari Jamhari (Agro Ekonomi, 2014)
The aims of this research are (1) determine the feasibility, (2) estimate the contribution of fisheries to the household income and (3) formulate business development strategies for seeding and enlargement of the tilapia catfish and carp comoditiesy   Sleman regency.Purposive sampling was used and the following locatios District Ngemplak, Moyudan, and Minggir. Data collection was perfomed proptionally interviewing 15 farmers in hatchery operations and enlargement of catfish, tilapia, and carp. The feasibility analysis tools used was the analysis of costs and revenues, financial analysis that includes the Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost (Net B/C), Payback Period (PP), and Break Event Point (BEP). Descriptive analysis was used for contributions to household income. The formulation of the strategy was carried out by the SWOT matrix analysis.The feasibility analysis result are NPV hatchery of catfish Rp. 193.091.118, NPV enlargement of catfish Rp 17.943.762, NPV hatchery of tilapia Rp 60.162.636, NPV of enlargement of tilapia Rp 31.850.378, NPV hatchery of carp Rp 44.981.614, and NPV enlargement of carp Rp 39.507.351. IRR hatchery of catfish 66%. IRR enlargement of catfish 29%. IRR hatchery of tilapia 63% IRR enlargement of tilapia 77%, IRR hatchery of carp 33% and IRR enlargement of carp 52%. Net B/C hatchery of catfish 1,57, Net B/C enlargement of catfish 1,08, Net B/C hatchery of tilapia 1,48, Net B/C enlargement of tilapia 1,65, Net B/C hatchery of carp 1,09 and Net B/C enlargement of carp 1,63. The payback period below 3 years. Fish farming contributes to the monthly family income at 48,87% and is above the minimum regional wages in Sleman. Thus the cultivation of freshwater fish in Sleman is feasible because it is profitable and can incease the family income. Aquaculture business development strategies can be applied based on the SWOT matrix and the feasibility result that include innovation, taking advantage of the simplicity of production and infrastructure factors that support freshwater fish farming and increasing the role of entrepeneurs and the stakholders through the development if technology and information.